Factors Associated With the General Public Knowledge and Awareness of Cardiovascular Diseases and its Risk Factors in Penang – Malaysia - Mostafa, Arwa Mohamed Amin; Mostafa, Hamza; Sarriff, Azmi (International Organization of Scientific Resaerch (IOSR), 2014)
Cardiovascular diseases(CVDs) are the top of the ten causes of hospital deaths in Malaysia. Increasing knowledge and awareness on CVDs and its risk factors is crucial for the prevention of CVDs. Identification of factors which are associated with the knowledge and awareness is important for the proper design of future awareness programs.This study was carried out to find out factors which are associated with the current knowledge and awareness of cardiovascular diseases (CVDs) and its risk factors among the general public in Penang-Malaysia.